Warehouse Storage Management of Wheat and Their Role in Food Security - Kumar, Chandrasen; Ram, C. L.; Jha, S. N.; Vishwakarma, R. K. (Frontiers in Sustainable Food Systems, 2021)
Silo storage is considered the best option for wheat storage. However, the storage losses in warehouse storage are also equivalent to silo storage of wheat when proper storage management practices are adopted and the Food Corporation of India (FCI) is the best example of a sustainable food storage system with only 0.3% storage losses in 3 years of wheat storage. The wheat procurement, storage, and distribution system of FCI is unique in the world and handles about 85 million tonnes of food grains annually by procuring from farmers at the guaranteed Minimum Support Price that meets certain quality standards. This article discusses the role of FCI in food security, warehouse storage management practice as a model, and storage loss level of wheat during storage.